Structural vibration serviceability: New design framework featuring human-structure interaction. (1st April 2017) - Shahabpoor, Erfan; Pavic, Aleksandar; Racic, Vitomir
Highlights: A new method is proposed for vibration serviceability assessment of pedestrian structures. It takes into account inter- and intra-subject variability of pedestrians. It features the interaction of each pedestrian with the occupied structure. The method is based on the experience of each pedestrian from structural vibration. The method is accurate and practical and shows low sensitivity to input variations. Abstract: Predicting the effect of walking traffic on structural vibrations is a great challenge to designers of pedestrian structures, such as footbridges and floors. This is mainly due to the lack of adequate design guidelines, which in turn can be blamed on poor research findings. Even the fundamental data are very rare and limited. This study proposes a new and more reliable method for serviceability assessment of the vertical vibrations induced by multi-pedestrian walking traffic. Key novelties include modelling the natural variability of the walking forces and the human bodies, as well as their individual interaction with the supporting structure at their moving location . Moreover, a novel approach to vibration serviceability assessment (VSA) is proposed based on the actual level of vibration experienced by each pedestrian, rather than the typical maximum vibration response at a fixed point. Application of this method on two full-scale footbridge structures have shown that, with a suitable calibration of human model parameters, the proposed method can predict the occupied structure modal frequency with less than 0.1% error and - more importantly - modal damping ratio with less than 1% error. The new method also estimated the structural responses with considerably less error (5–10%) compared to a selection of current design guidelines (200–500%). The proposed VSA method is not suitable for hand-based calculations. However, if coded and materialised as a user-friendly software, it can be incorporated into design guidelines and used by consultants in everyday engineering practice.